Improving the monitoring of the value of implicit guarantees for bank debt - Schich, Sebastian (OECD Publishing, 2014)
The value of implicit guarantees has declined from its peak at the height of the financial crisis, which is consistent with progress made regarding the bank regulatory reform agenda, as one would expect that many of the reform measures imply a more limited value of implicit guarantees for bank debt. Implicit guarantees persist however and their value continues to be significant, estimated here to be equivalent to EUR 50 billion of annual funding costs savings for a sample of more than 100 large European banks. This estimated funding cost advantage is a conservative estimate as it only focuses on one type of debt that can be measured in "real-time", that is as data on credit ratings, debt issuance and prices of debt become available. In any case, bank debt continues to be considered "special" by market participants and this observation implies that the substantial economic distortions, including distortions to risk-taking incentives and competition, arising from this situation also persist
Keywords: Finance and Investment